1986
DOI: 10.1083/jcb.103.5.1781
|View full text |Cite
|
Sign up to set email alerts
|

Cell proliferation and expression of the transferrin receptor gene: promoter sequence homologies and protein interactions.

Abstract: Abstract. A 365-bp fragment from the 5' region of the human transferrin receptor gene has been subcloned and sequenced. This fragment contains 115 bp of flanking sequence, the first exon, and a portion of the first intron. It contains a TATA box, several GC-rich regions, and is able to efficiently promote expression of the bacterial CAT gene in mouse 3T3 cells. Sequence comparisons demonstrate that this DNA segment has homology to the promoter regions of the human dihydrofolate reductase gene and the mouse int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
40
0

Year Published

1987
1987
2003
2003

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…All three stable cell lines initiated DNA synthesis between 8 and 12 h and reached a maximum level around 18 h post serum stimulation. Thus, all of the cell lines responded to serum in nearly identical manners and retained the temporal pattern of the parental 3T3 cell line (28).…”
Section: Methodsmentioning
confidence: 92%
See 2 more Smart Citations
“…All three stable cell lines initiated DNA synthesis between 8 and 12 h and reached a maximum level around 18 h post serum stimulation. Thus, all of the cell lines responded to serum in nearly identical manners and retained the temporal pattern of the parental 3T3 cell line (28).…”
Section: Methodsmentioning
confidence: 92%
“…The boxes labelled A and B represent regions of the promoter that were previously shown to be protected by factors from HeLa nuclear extracts in DNase I footprinting experiments (3,26,28). Both sites have sequences that are similar to the consensus recognition sites of known transcription factors.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…20 Expression of TfR1 is regulated at the levels of transcription and posttranscription by factors such as cellular status of iron, oxygen, proliferation, and differentiation. [21][22][23][24][25][26] Expression profiles of TfR1 and TfR2 in response to cellular iron status were also different. Intracellular iron levels regulate expression of TfR1 mainly at a posttranscriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested that this sequence may be recognized by a T-cell-specific DNAbinding protein (14). The 5' flanking region also contains a 20-bp sequence (GGGGCGGGCCGGGGCGGGGCTC) (bp -75 to -54) which is present in a similar location in the thymidine kinase gene (12), the dihydrofolate reductase (DHFR) gene (41), and the transferring receptor (TR) gene (Table 1) (30). This sequence is very G+C rich and contains two tandemly arrayed potential binding sites for the Spl transcription factor (GGGGCGG) (10).…”
mentioning
confidence: 99%